The Determinants of Job Promotion Among Civil Servants in South Sulawesi: a PLS-SEM Study - Hendrawati Hamid (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2022)
This study aims to examine the factors that influence the job promotion of state civil servants (PNS) in South Sulawesi. This research is classified as explanatory as it explains the causal effect between exogenous (education and training, organizational culture) and endogenous (performance and job promotion) variables. Due to the large population, the most appropriate sampling technique was purposive sampling. After the primary data collection process through questionnaires, there were 42 PNS Sul-Sel that met the criteria were netted and selected as respondents. Furthermore, based on the data characteristics, PLS-SEM data analysis was applied. The results showed that among the seven hypotheses tested, six were accepted, while one was rejected. Implications and suggestions are discussed further.